Praxishandbuch Bibliotheksbau Planung - Gestaltung - Betrieb - Hauke, Petra 1946-; Werner, Klaus Ulrich 1956- (De Gruyter Reference, 2016)
The Practical Handbook of Library Constructiondeals with all aspects of building and equipping a library. It covers planning, site selection, exterior facilities, space allotment, tendering, financing, laws and standards, library facilities, technical infrastructure, transport systems, classroom spaces, and barrier-free design. The handbook includes an extensive bibliography. Petra Hauke, Humboldt-Universität, Berlin und Klaus Ulrich Werner, Freie Universität Berlin.